2004
DOI: 10.1152/ajprenal.00219.2003
|View full text |Cite
|
Sign up to set email alerts
|

SLC26A7: a basolateral Cl-/HCO3-exchanger specific to intercalated cells of the outer medullary collecting duct

Abstract: The outer medullary collecting duct (OMCD) plays an important role in bicarbonate reabsorption and acid-base regulation. An apical V-type H+-ATPase and a basolateral [Formula: see text] exchanger, located in intercalated cells of OMCD, mediate the bicarbonate reabsorption. Here we report the identification of a new basolateral [Formula: see text] exchanger in OMCD intercalated cells in rat kidney. Northern hybridizations demonstrated the predominant expression of this transporter, also known as SLC26A7, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
103
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 41 publications
9
103
3
Order By: Relevance
“…BB666404) and an antibody raised against human SLC26A7 were used for immunofluorescence labeling (8,19).…”
Section: Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…BB666404) and an antibody raised against human SLC26A7 were used for immunofluorescence labeling (8,19).…”
Section: Antibodiesmentioning
confidence: 99%
“…Functional and molecular studies from our laboratory demonstrated that SLC26A7 is a chloride/bicarbonate exchanger (7). In the stomach, SLC26A7 is expressed on the basolateral membrane of the acid-secreting gastric parietal cells (7), whereas in the kidney, it localizes on the basolateral membrane of acid-secreting A-intercalated (A-IC) cells of the outer medullary collecting duct (OMCD) (8,19). OMCD has the highest rate of acid secretion among the collecting duct segments (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Cl Ϫ and formate, SLC26A6 has affinities for oxalate, HCO 3 Ϫ , and SO 4 2Ϫ (39,93). SLC26A7 has been localized to the BLM of rat outer medullary collecting duct cells where it has been hypothesized to function in HCO 3 Ϫ reabsorption (63). When expressed in Xenopus oocytes, SLC26A7 exhibits HCO 3 Ϫ , Cl Ϫ , oxalate, and SO 4 2Ϫ transport activity (47,63).…”
Section: Tubular Somentioning
confidence: 99%
“…SLC26A7 has been localized to the BLM of rat outer medullary collecting duct cells where it has been hypothesized to function in HCO 3 Ϫ reabsorption (63). When expressed in Xenopus oocytes, SLC26A7 exhibits HCO 3 Ϫ , Cl Ϫ , oxalate, and SO 4 2Ϫ transport activity (47,63). SLC26A11 mRNA transcript is present in the mammalian kidney and displays DIDS-sensitive Na ϩ -independent SO 4 2Ϫ transport when expressed in insect Sf9 cells (92).…”
Section: Tubular Somentioning
confidence: 99%